Stochastic simplified modelling of abrasive waterjet footprints - Torrubia, P. Lozano; Billingham, John; Axinte, Dragos A. (Royal Society, 2016)
Abrasive micro-waterjet processing is a non-conventional machining method that can be used to manufacture complex shapes in difficult-to-cut materials. Predicting the effect of the jet on the surface for a given set of machine parameters is a key element of controlling the process. However, the noise of the process is significant, making it difficult to design reliable jet-path strategies that produce good quality parts via controlled-depth milling. The process is highly unstable and has a strong random component that can affect the quality of the workpiece, especially in the case of controlled-depth milling. This study describes a method to predict the variability of the jet footprint for different jet feed speeds. A stochastic partial differential equation is used to describe the etched surface as the jet is moved over it, assuming that the erosion process can be divided into two main components: a deterministic part that corresponds to the average erosion of the jet, and a stochastic part that accounts for the noise generated at different stages of the process. The model predicts the variability of the trench profiles to within<8%. These advances could enable abrasive micro-waterjet technology as a suitable technology for controlled-depth milling.